Answers ( )

    0
    2021-08-02T03:28:15+00:00

    Step-by-step explanation:

    8-²+9-²+6-²

    =√8+√9+√6

    =2√2+3+√6

    =5√2+√6

    0
    2021-08-02T03:28:26+00:00

    Answer:

     \frac{289}{5184}  \\

    Step-by-step explanation:

    ( {8}^{ - 2}  +  {9}^{ - 2}  +  {6}^{ - 2} ) \\  \\  = ( \frac{1}{ {8}^{2} }  +  \frac{1}{ {9}^{2} }  +  \frac{1}{ {6}^{2} } ) \\  \\  = ( \frac{1}{64}  +  \frac{1}{81}  +  \frac{1}{36} ) \\  \\  (lcm \: of \: 64 \: 81 \: and \: 36 \: is \: 5184) \\   \\  = ( \frac{(1 \times 81) + (1 \times 64) + (1 \times 144)}{5184}  \\  \\  = ( \frac{81 + 64 + 144}{5184})  \\  \\  =  \frac{289}{5184}

    Hence

     {9}^{ - 2}  +  {8}^{ - 2}  +  {6}^{ - 2}  =  \frac{289}{5184}

    hope it helps.

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )